Kinematic and static analyses of the pedaling by means of new slider-crank mechanism - Yoshizawa, Y.; Watanabe, K.; Niizeki, K. (Journal of Biomechanical Science and Engineering, 2007)
A slider-crank mechanism whose coupler curve is the approximate ellipse is designed so that a man may perform the pedaling of the elliptical motion of the foot. Because the thigh, the shank and the foot constitute the three-link chain, the system of a man and the bicycle with the slider-crank pedal mechanism is the planar seven-link mechanism with two degree freedom. The system of a man and the ordinary bicycle is the planar five-link mechanism with two degree freedom. Kinematic characteristics of these systems are analyzed with the given pattern of the pedal angle curve during a crank rotation. Then, the crank moment and the pin joint forces of these systems are calculated for given patterns of the hip moment and the knee moment during a crank rotation and the average crank moment are estimated. It makes comparative study of calculated and experiment results of the pedal force, the crank moment and physiological results of oxygen uptake and carbon dioxide output in usual crank pedaling and in slider crank pedaling.